2016
DOI: 10.1530/jme-15-0279
|View full text |Cite
|
Sign up to set email alerts
|

Acute anorexigenic action of leptin in rainbow trout is mediated by the hypothalamic Pi3k pathway

Abstract: Leptin (Lep) is an anorexigenic hormone and regulates appetite-related neuropeptides in mammals. A number of neuropeptides have also been linked to appetite regulation in teleost fish, but Lep signaling activation and effects on appetite-regulating neurons are poorly elucidated in early vertebrates. This study uses cellular, tissue and organismal approaches to elucidate the acute, central Lep action in rainbow trout. The results demonstrate that Lep activates phosphorylation of protein kinase B (Akt) and signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…Leptin treatment is usually anorectic in fish as demonstrated studies in rainbow trout (Murashita et al, 2008; Kling et al, 2009; Aguilar et al, 2010; Gong et al, 2016a), goldfish (Volkoff et al, 2003; de Pedro et al, 2006; Vivas et al, 2011) and striped bass (Won et al, 2012). This anorectic effect occurred in parallel with changes in the expression of neuropeptides generally indicating an enhanced anorexigenic potential.…”
Section: Endocrine Modulation Of Nutrient Sensingmentioning
confidence: 99%
See 2 more Smart Citations
“…Leptin treatment is usually anorectic in fish as demonstrated studies in rainbow trout (Murashita et al, 2008; Kling et al, 2009; Aguilar et al, 2010; Gong et al, 2016a), goldfish (Volkoff et al, 2003; de Pedro et al, 2006; Vivas et al, 2011) and striped bass (Won et al, 2012). This anorectic effect occurred in parallel with changes in the expression of neuropeptides generally indicating an enhanced anorexigenic potential.…”
Section: Endocrine Modulation Of Nutrient Sensingmentioning
confidence: 99%
“…Indeed, Librán-Pérez et al (2015b) demonstrated that protein levels of AMPK, Akt, and mTOR increased in hypothalamus of fish fed a lipid-enriched diet. Furthermore, Gong et al (2016a) demonstrated increased Akt protein levels in isolated hypothalamic cells incubated with leptin. Finally, Velasco et al (2016b) also suggested the possible involvement of ceramides in the connection between activation of hypothalamic fatty acid sensing systems, neuropeptide mRNA abundance, and control of food intake.…”
Section: Impact Of Nutrient Sensing On Food Intake Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In goldfish, leptin injections decrease feeding and locomotor behavior (Volkoff et al, 2003; de Pedro et al, 2006; Vivas et al, 2011; Tinoco et al, 2012) in part by stimulating anorexigenic sytems (e.g., CART, CCK, and POMC) and inhibiting orexigenic ones (e.g., orexin, NPY, AgRP) (Volkoff et al, 2003; Yan et al, 2016). Similarly, in rainbow trout (Salmoniforme), central leptin administration suppresses food intake and increases the hypothalamic expressions of CART and POMC (Gong et al, 2016). Leptin treatment also inhibits feeding in grass carp (Li et al, 2010) (Cypriniforme) and increases energy expenditure in zebrafish larvae (Renquist et al, 2013).…”
Section: Hormones Involved In Food Intakementioning
confidence: 99%
“…Recent study has demonstrated that PI3K signaling participates in the regulation of neuropeptide Y-and proopiomelanocortin-mediated appetite suppression (Chu et al 2014). Furthermore, involvement of the PI3K/Akt pathway in the appetite regulation has been suggested in diff erent study (Gong et al 2015). Activation of oxytocin receptor is associated with PI3K and extracellular signalregulated kinase signaling pathways (Lin et al 2012).…”
Section: Neuropeptide Actions Depend On Phosphoinositide 3-kinasementioning
confidence: 99%